PENINGKATAN KOMPETENSI MENULIS PARAGRAF DENGAN METODE BIMBINGAN BERANTAI BERHADIAH - Nuning Suistiningsih (Jurnal Cakrawala Pendidikan, 2009)
This study aimed to (1) develop the chained-reward tutorial technique in the Indonesian language learning, (2) improve competence in writing deductive and inductive paragraphs among Year XI students of IPA1 SMAN 1 Depok, and (3) develop remedial and enrichment programs in the teaching and learning process. This study was a classroom research study consisting of two cycles. Each cycle consisted of planning, action, observation, and reflection. The action focused on the empowerment of the students who had attained the mastery level to guide those who had not attained it in a chain, both by teachers and students alternately. The research setting was SMAN 1 Depok. The research subjects were 42 Year XI students in the third semester in the academic year 2008-2009, consisting 16 male students and 26 female students. The criterion for the subject selection was that the students had good academic achievement but poor ability in writing deductive and inductive paragraphs. The data were collected through observations, documents, field notes, tests, and student questionnaire. The data were analyzed using a qualitative technique, namely the interactive analysis technique developed by Miles and Huberman. The results of the research showed that the chained-reward tutorial method applied in two cycles managed to improve competence in writing deductive and inductive paragraphs and develop remedial and enrichment activities in learning. Keywords: chained-reward tutorial method, deductive and inductive paragraphs